Study on gastronomic cultures of post-Neolithic civilizations in Anatolia. Issue 5 (3rd September 2019) - Oktay, Serdar
ABSTRACT: With the fact that people started to lead a communal life in Anatolia, states began to be established, and different civilizations emerged consecutively. For centuries, these state chains have caused Anatolia to become the cradle of civilizations. In our article, the transition to agriculture, historical gastronomies and interactions of civilizations appearing in the chronology starting from the place where the first settlement in Anatolia was observed along with the Neolithic Age, Chalcolithic Age, Bronze Age and Iron Age until today were investigated, and it was attempted to determine the effects of gastronomic cultures of the countries, that lived in Anatolian geography for centuries and that are existing at the present time by settling in various geographies of the world, on each other. Regarding gastronomy, archaeological excavations in Anatolia in the Urfa province of Göbeklitepe discovered a settlement dating back 11 thousand years BC where they reached the human bones of the hunter gatherer. We see the Hattians, Assyrians, Hittites, Phrygians, Lydians, Ionians, Lycians and Urartians in the resulting picture. After this period, the Persians, Romans and Byzantines ruled in Anatolia.